Raloxifene Stimulates Estrogen Signaling to Protect Against Age- and Sex-Related Intervertebral Disc Degeneration in Mice - Bhadouria, Neharika; Berman, Alycia G.; Wallace, Joseph M.; Holguin, Nilsson (Frontiers in Bioengineering and Biotechnology, 2022)
Estrogen agonist raloxifene is an FDA-approved treatment for osteoporosis in postmenopausal women that may also be a promising prophylactic for painful intervertebral disc (IVD) degeneration. Here, we hypothesized that (1) aging and biological sex contribute to IVD degeneration by reducing estrogen signaling and that (2) raloxifene stimulates estrogen signaling to protect against age- and sex-related IVD degeneration in mice. 2.5-month-old (male and female) and 22.5-month-old (female) C57Bl/6J mice were subcutaneously injected with raloxifene hydrochloride 5x/week for 6 weeks (n=7-9/grp). Next, female mice were ovariectomized (OVX) or sham-operated at 4-months of age and tissues harvested at 6-months (n=5-6/grp). Advanced aging and OVX increased IVD degeneration score, weakened IVD strength, reduced estrogen receptor-α (ER-α) protein expression and increased neurotransmitter substance P (SP) expression. Similar to aging and compared to male IVDs, female IVDs were more degenerated, mechanically less viscoelastic and expressed less ER-α protein but, unlike the effect induced by aging or OVX, IVD mechanical force was greater in females than males. Therapeutically, systemic injection of raloxifene promoted ER-α protein to quell these dysregulations by enlarging IVD height, alleviating IVD degeneration score, increasing the strength and viscoelastic properties of the IVD, and reducing IVD cell expression of SP in young-adult and old female mice. Transcriptionally, injection of raloxifene upregulated the gene expression of ER-α and extracellular matrix-related anabolism in young-adult and old IVD. In vertebra, advanced aging and OVX reduced trabecular BV/TV, whereas injection of raloxifene increased trabecular BV/TV in young-adult and old female mice, but not in male mice. In vertebra, advanced aging, OVX and biological sex (females>males) increased the number of SP-expressing osteocytes, whereas injection of raloxifene reduced the number of SP-expressing osteocytes in young-adult female and male mice and old female mice. Overall, injection of estrogen agonist raloxifene in mice normalized dysregulation of IVD structure, IVD mechanics and pain-related SP expression in IVD cells and osteocytes induced by aging and biological sex. These data suggest that, in addition to bone loss, raloxifene may relieve painful IVD degeneration in postmenopausal women induced by advanced age, biological sex and estrogen-depletion.